Pengaruh Brand Image dan Brand Awareness terhadap Brand Loyalty pada Pengguna Provider Telkomsel di Surabaya - Sinta Kurnia Illahi; Sonia Andarini (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
The internet is a necessity, this makes the Telkomsel company strive to carry out marketing activities. Marketing activities are expected to create brand image, brand awareness and brand loyalty. This study aims to examine the effect of brand image on brand loyalty of Telkomsel provider users in Surabaya. Data collection techniques using literature studies and questionnaires. Data were analyzed using PLS (Partial Least Square). By using the Wibisono formula, the number of samples used in this study was 100 respondents. The results showed that brand image and brand awareness had a significant effect on brand loyalty to Telkomsel provider users in Surabaya. Keywords: Brand Image, Brand Awareness, Brand Loyalty